Detailed low temperature studies on thermoelectric performance of K-doped Bi2Ca2Co2Oy ceramics fibers. (1st August 2022) - Özçelik, C; Depci, T; Çetin, G; Gürsul, M; Özçelik, B; Madre, M A; Sotelo, A; Ando, H; Terashima, K; Takano, Y
Abstract: The effect of K substitution for Ca in Bi2 Ca2-x Kx Co2 Oy (x = 0.0, 0.05, 0.075, 0.10, and 0.125) thermoelectric ceramics, produced via laser floating zone (LFZ) method, have been systematically investigated. XRD patterns are quite similar for all samples and main peaks in the patterns correspond to reflection planes of the thermoelectric phase together with small amount of secondary phases. SEM micrographs revealed well oriented grains along the growth direction, and the presence of three different contrasts, associated through EDS to different phases, namely, black (Co oxide), white (Bi poor phase) and grey (Bi2 Ca2 Co1.7 Oy TE phase). It was also seen that the amount of secondary phases diminishes with K-increase. The room-temperature resistivity values sharply decrease from 0.75 mΩ.m for the undoped sample to 0.44 mΩ.m for the 0.05 K-doped one, increasing for higher doping. Seebeck coefficient also decreases from 190 μ V K −1 in the pristine sample, to 160 μ V K −1 in all the K-doped ones, at 390 K. Thermal conductivity increases with temperature up to around 250 K, decreasing at higher temperatures. Thermal conductivity at 390 K decreases from 1.1 W K −1 m −1 in the pristine sample to lower values by K-doping, reaching the minimum, 0.9 W K −1 m −1, in the 0.125 K-doped one. As a result, the highest ZT value of has been determined in 0.05 K-doped sample, around 0.021 at 390 K.